Ketahanan Perbankan Syariah Indonesia Terhadap Fluktuasi Kondisi Makroekonomi dan Kondisi Fundamental Saat Pandemi Covid-19 - Yuningsih, Ayu; Alfiah, Esti (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2022)
The Covid-19 pandemic has forced all sectors, especially the financial institution sector, to work hard to maintain their institutions to be able to generate profits under fluctuating conditions. Therefore, this study aims to analyze the resilience of Islamic banking in maintaining its profitability amidst fluctuations in macroeconomic conditions and fundamental conditions during the COVID-19 pandemic. This study uses a quantitative approach and is based on time series data (ime series). This research was conducted at Islamic Commercial Banks in Indonesia. The data used is secondary data which includes data on Return On Assets (ROA), Non Performing Financing (NPF), Financing to Deposite Ratio (FDR) obtained from SPS OJK, economic growth data (IPI), obtained from the official website of Bank Indonesia. (BI), and data on inflation and interest rates (BI Rate) obtained from the official website of the Central Statistics Agency (BPS). The data used is aggregated data that is presented monthly for the period January 2016 to March 2021. Data analysis in this study uses a vector error correction model (VECM) as an approach to see short-term relationships, and cointegration tests as an approach to see indications of long-term relationships. . The results showed that the profitability of Islamic banking is influenced by macroeconomic conditions, namely inflation. Meanwhile, the IPI and BI Rate do not have a significant effect on the profitability of Islamic banking. Likewise, the fundamental conditions of Islamic banking, NPF and FDR do not have a significant influence on the profitability of Islamic banking.